2004
DOI: 10.1128/jb.186.12.3712-3720.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Type II Protein Secretion System of Legionella pneumophila Promotes Growth at Low Temperatures

Abstract: The gram-negative bacterium Legionella pneumophila grows in both natural and man-made water systems and in the mammalian lung as a facultative intracellular parasite. The PilD prepilin peptidase of L. pneumophila promotes type IV pilus biogenesis and type II protein secretion. Whereas pili enhance adherence, Legionella type II secretion is critical for intracellular growth and virulence. Previously, we observed that pilD transcript levels are greater in legionellae grown at 30 versus 37°C. Using a new pilD::la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 89 publications
2
64
0
1
Order By: Relevance
“…pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells. This is expected, as L. pneumophila shows increased expression of the flagellum and of type IV pili, both of which have been described in other bacteria to be involved in adhesion (O'Toole & Kolter, 1998;Pratt & Kolter, 1998;Watnick & Kolter, 1999), in stationary phase during low-temperature growth (Heuner et al, 1999;Soderberg et al, 2004). Because stationary phase mimics the transmissive phase in which bacteria are released from amoebae (Molofsky & Swanson, 2004), our observations suggest that bacteria that exit host cells in natural lowtemperature environments are in an optimal physiological state to adhere to biofilms.…”
Section: Discussionmentioning
confidence: 53%
“…pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells. This is expected, as L. pneumophila shows increased expression of the flagellum and of type IV pili, both of which have been described in other bacteria to be involved in adhesion (O'Toole & Kolter, 1998;Pratt & Kolter, 1998;Watnick & Kolter, 1999), in stationary phase during low-temperature growth (Heuner et al, 1999;Soderberg et al, 2004). Because stationary phase mimics the transmissive phase in which bacteria are released from amoebae (Molofsky & Swanson, 2004), our observations suggest that bacteria that exit host cells in natural lowtemperature environments are in an optimal physiological state to adhere to biofilms.…”
Section: Discussionmentioning
confidence: 53%
“…Since L. pneumophila survives and replicates at temperatures ranging from 4 to 63°C (33,42,73) and since siderophore expression is elevated at lower temperatures in some other aquatic bacteria (14), strain 130b was grown in deferrated CDM at 25°C and 37°C, and supernatants were tested in the CAS assay (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The outer membrane alterations might be responsible for the slowgrowth phenotype noted for T2S mutants of V. cholerae (39,64,77). Although no outer membrane changes have been reported for T2S mutants of Legionella pneumophila, they also display reduced growth rates under certain growth conditions (82).…”
mentioning
confidence: 93%